2002
DOI: 10.1002/mrdd.10004
|View full text |Cite
|
Sign up to set email alerts
|

In utero infection and adult schizophrenia

Abstract: We review emerging evidence indicating that in utero exposure to infection is a risk factor for schizophrenia. It is hypothesized that a prenatal infection increases the liability to schizophrenia in adulthood by adversely affecting the maturation of critical brain structural and functional components implicated in the pathogenesis and pathophysiology of the disorder. Early evidence for a role of in utero infection includes investigations linking schizophrenia with birth during the winter and in urban regions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
131
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(136 citation statements)
references
References 43 publications
1
131
0
4
Order By: Relevance
“…Maternal infection during pregnancy increases the risk for several neuropsychiatric disorders in the offspring, including schizophrenia (Brown and Susser, 2002;Fatemi, 2005) and autism (Rodier and Hyman, 1998;Miller et al, 2005). Recent attempts to model this epidemiological link in animals has yielded considerable support for a causal relationship between in utero immune activation and the emergence of adult psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal infection during pregnancy increases the risk for several neuropsychiatric disorders in the offspring, including schizophrenia (Brown and Susser, 2002;Fatemi, 2005) and autism (Rodier and Hyman, 1998;Miller et al, 2005). Recent attempts to model this epidemiological link in animals has yielded considerable support for a causal relationship between in utero immune activation and the emergence of adult psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…3 Epidemiological studies have indicated that maternal infections during pregnancy increase the risk for these disorders in the offspring. [4][5][6][7] According to one hypothesis, the maternal cytokine response to infections may play a crucial role in this association, 8 because the induction of cytokines is a fundamental immunological event triggered by virtually any infection. 9 More specifically, it has been suggested that activation of pro-inflammatory cytokines, including interleukin (IL)-1b, IL-6 and tumor necrosis factor (TNF)-a, mediate the neurodevelopmental effects of maternal infections on the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal exposure, during pregnancy, to influenza (Brown et al, 2004a;Mednick et al, 1988), poliovirus (Suvisaari et al, 1999), rubella, measles, varicella-zoster (Brown and Susser, 2002), retrovirus (Yolken et al, 2000), and bacterial agents (O'Callaghan et al, 1994), has been associated with an increased risk for schizophrenia in the offspring. This suggests that a maternal immune response, common to various infectious agents, could influence fetal brain development and, consequently, lead to schizophrenia.…”
Section: Introductionmentioning
confidence: 99%